Effects of objectifying gaze on female cognitive performance: The role of flow experience and internalization of beauty ideals. (1st November 2016) - Guizzo, Francesca; Cadinu, Mara
Abstract : Although previous research has demonstrated that objectification impairs female cognitive performance, no research to date has investigated the mechanisms underlying such decrement. Therefore, we tested the role of flow experience as one mechanism leading to performance decrement under sexual objectification. Gaze gender was manipulated by having male versus female experimenters take body pictures of female participants ( N = 107) who then performed a Sustained Attention to Response Task. As predicted, a moderated mediation model showed that under male versus female gaze, higher internalization of beauty ideals was associated with lower flow, which in turn decreased performance. The implications of these results are discussed in relation to objectification theory and strategies to prevent sexually objectifying experiences.